Secondary Equity Offerings Long Run Underperformance: Puzzle or Mistake - Har, Wong Pik; Visvanathan, Karthiyayini (Asian Economic and Financial Review, 2018)
This study examines whether misvaluation which causes long run underperformance is present when firms issue additional equity and if firms time the additional equity issue when market as a whole overvalues the firms, in order to capitalise on the value appreciation. The overvaluation is measured as the difference between the market value of the issuing firm 30 days prior to the equity issue date and the fundamental value of the firm 1 year prior to the day of equity issue. The fundamental value is quantified using the residual income valuation method. The results are partially consistent with the existing empirical literature, as misvaluation is present when firms issue additional equity. However, firms do not specifically time the issuance of equity with overall market overvaluation as based on the results collected, more additional equity were issued when misvaluation levels were lower.